Proceso de Autorregulación del Aprendizaje en Estudiantes de Psicología de la Universidad Antonio Nariño Durante Pandemia por COVID19 - Gómez Romano, Cristian Andrés (Universidad Antonio Nariño, 2022)
This research refers to the process of self-regulation of learning in ninth semester students in Psychology at the Antonio Nariño University during a COVID19 pandemic. The objective was to describe the process of self-regulation of learning in remote education during the COVID 19 pandemic, in students of the ninth semester in Psychology at the Antonio Nariño University, where it was specified how the planning phase is in students to develop the different academic tasks , also describing the phase of execution of the tasks, partials and academic activities in university students in the process of carrying out tasks and identifying how the self-reflection phase is presented in the self-evaluation process, to know the motivations of the student, in front of the work your learning process. The research methodology was carried out from a qualitative approach, with a descriptive design, collecting information through an open response survey, where the following categories were handled: planning phase, execution phase and self-reflection phase, having Considering Zimmerman as a theoretical basis, therefore, the epistemological criterion that was taken in this work was the phenomenological one.